Signalling Significance Of Distributions To Shareholders: A Study Of Cash Dividends, Stock Dividends, And Stock Repurchases In The Malaysian Corporate Sector - Kok, Lee Kuin (2008)
Companies follow various methods to distribute dividends to shareholders in return for the latter's subscription to their equity capital. The objective of the present study is to identify the wealth effects and signalling significance of the above mentioned distribution methods followed by the companies in Malaysia.